The causality between gut microbiome and liver cirrhosis: a bi-directional two-sample Mendelian randomization analysis - Xiao, Qing-Ao; Yang, Yun-Fei; Chen, Lin; Xie, Ying-Chun; Li, Hai-Tao; Fu, Zhi-Gang; Han, Qiang; Qin, Jia; Tian, Jie; Zhao, Wen-Jiang; Cai, Fei; Hu, Yin-Tao; et al. (Frontiers in Microbiology, 2023)
Background and Aim:Previous studies have reported an association between gut microbiota and cirrhosis. However, the causality between intestinal flora and liver cirrhosis still remains unclear. In this study, bi-directional Mendelian randomization (MR) analysis was used to ascertain the potential causal effect between gut microbes and cirrhosis. Methods:Large-scale Genome Wide Association Study (GWAS) data of cirrhosis and gut microbes were obtained from FinnGen, Mibiogen consortium and a GWAS meta-analysis of Alcoholic cirrhosis (ALC). Two-sample MR was performed to determine the causal relationship between gut microbiota and cirrhosis. Furthermore, a bi-directional MR analysis was employed to examine the direction of the causal relations. Result:In MR analysis, we found that 21 gut microbiotas were potential associated with cirrhosis. In reverse MR analysis, 11 gut microbiotas displayed potential significant associations between genetic liability in the gut microbiome and cirrhosis. We found that Family Lachnospiraceae (OR: 1.59, 95% CI:1.10-2.29) might be a harmful bacterium in cirrhotic conditions (ICD-10: K74). Furthermore, Genus Erysipelatoclostridium might be a protective factor for cirrhosis (OR:0.55, 95% CI:0.34-0.88) and PBC (OR:0.68, 95% CI:0.52-0.89). Combining the results from the MR analysis and reverse MR analysis, we firstly identified the Genus Butyricicoccus had the bi-directional causal effect on PBC (Forward: OR:0.37, 95% CI:0.15-0.93; Reverse: OR:1.03, 95% CI:1.00-1.05). Conclusion:We found some new potential causal effect between cirrhosis and intestinal flora,and provided new insights into the role of gut microbiota in the pathological progression of liver cirrhosis.